2015
DOI: 10.1080/13607863.2015.1072795
|View full text |Cite
|
Sign up to set email alerts
|

Concerns about aging and caregiving among middle-aged and older lesbian and gay adults

Abstract: These findings suggest needed areas of support and programs for older gay men and lesbian women. They also suggest that healthcare professionals might need more training regarding the particular needs and concerns of this community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(39 citation statements)
references
References 22 publications
2
30
0
7
Order By: Relevance
“…Literature that addresses homosexuality and ageing simultaneously is non-extensive and tends to fall into the following topics (Cahill & Valadéz, 2013;Czaja et al, 2015;Grossman, D'Augelli, & O'Connell, 2002;Muraco, Le Blanc, & Russell, 2008;Owen & Catalan, 2012): (a) myths and stereotypes about older lesbians and gay men; and (b) experiences of gay and lesbian seniors and their families avoiding health and social services in the community out of fear of discrimination. Scarcity of research on homosexual older people has been justified by many reasons (Berger, 1982;Berger & Kelly, 2002;Minichiello, Plummer, & Loxton, 2004): (i) gerontology, a young science, has had to deal with some of the many challenges of ageing (such as chronic disease or informal caregiving); (ii) homosexuals, in particular older ones, are still a population difficult to involve in research (mainly due to the fear of discrimination); and (iii) in general, society tends to stereotype older people as "asexual", so that the sexual orientation would be of no interest.…”
Section: Ageing and Homosexuality: The Case Of Older Gay Menmentioning
confidence: 99%
“…Literature that addresses homosexuality and ageing simultaneously is non-extensive and tends to fall into the following topics (Cahill & Valadéz, 2013;Czaja et al, 2015;Grossman, D'Augelli, & O'Connell, 2002;Muraco, Le Blanc, & Russell, 2008;Owen & Catalan, 2012): (a) myths and stereotypes about older lesbians and gay men; and (b) experiences of gay and lesbian seniors and their families avoiding health and social services in the community out of fear of discrimination. Scarcity of research on homosexual older people has been justified by many reasons (Berger, 1982;Berger & Kelly, 2002;Minichiello, Plummer, & Loxton, 2004): (i) gerontology, a young science, has had to deal with some of the many challenges of ageing (such as chronic disease or informal caregiving); (ii) homosexuals, in particular older ones, are still a population difficult to involve in research (mainly due to the fear of discrimination); and (iii) in general, society tends to stereotype older people as "asexual", so that the sexual orientation would be of no interest.…”
Section: Ageing and Homosexuality: The Case Of Older Gay Menmentioning
confidence: 99%
“…Studies have shown that LGBT aging adults may feel distrust toward health and social service agencies, and avoid or delay health care for fear of discrimination due to their sexual orientation or gender identity (Beeler, Rawls, Herdt, & Cohler, 1999;Brotman et al, 2003;Cahill, 2000;Cook-Daniels, 2006;Croghan et al, 2015;Wallace, Cochran, Durazo, & Ford, 2011). Incidents of overt homophobia or transphobia from healthcare providers toward older sexual and gender minority adults are common (Brotman et al, 2003;Cook-Daniels, 2015;Czaja et al, 2015). In one study, a respondent recalled, "when we got into the nursing home and they found out he was gay, they refunded him his money and threw him out" (Czaja et al, 2015).…”
Section: Thementioning
confidence: 99%
“…Incidents of overt homophobia or transphobia from healthcare providers toward older sexual and gender minority adults are common (Brotman et al, 2003;Cook-Daniels, 2015;Czaja et al, 2015). In one study, a respondent recalled, "when we got into the nursing home and they found out he was gay, they refunded him his money and threw him out" (Czaja et al, 2015).…”
Section: Thementioning
confidence: 99%
See 2 more Smart Citations